Digital Readiness of Creative Economy Entrepreneurs Subsector Culinary in Padang City - Maliha, Dabitha Wise (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The Covid-19 pandemic had an impact to culinary entrepreneurs begin to adapting digitalization. However, digitalization transformation process needed digital readiness to better prepared facing challenges in various crises. The purpose of this article is to analyze the extent of digital readiness and the use of digitalization by culinary entrepreneurs in Padang city. The analytical method used is descriptive analysis from data sources on Roadmap Creative Economy of Padang city from the 2021-2026. The results show that 51 culinary entrepreneurs are in the complement category and 50 culinary entrepreneurs are in the digital data-based company category. Culinary entrepreneurs also consider that using digital technology give benefit to reducing business costs and increasing business productivity. In addition, research and development, technology leadership and innovation are also considered important. However, the cost of using technology is not cheap and many of them do not have adequate financial resources to apply technology to business operations. They also worry that hackers can steal data. The use of digital technology provides the benefits of improving product quality (goods/services), customer service, and creating better working relationships with business partners. While the value of benefits that have not been maximized are related to competitive advantages that are not owned by competitors and reduced business costs.